2015
DOI: 10.22610/imbr.v7i3.1157
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Top Management Support and Internal Control of the Accounting Information Systems Quality and Its Implications on the Accounting Information Quality

Abstract: This study empirically examined the influences of the top management support and of the internal control on the accounting information system quality system. Besides, the accounting information system quality has an impact on the accounting information quality. To collect the data, a research instrument was prepared to participant. Using survey information collected from forty seven (47) Baitulmal Wattamwil (BMT) in West Java Indonesia those are applied accounting information system, this study uses path analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Regarding the first objective, which is aimed to analyze the influence of quality of ICS on quality of AIS, the results show that there is a positive and significant relationship between quality of ICS and quality of AIS, and that the first variable explains 28.4% of the variance of the second variable. The results support the first research hypothesis (H1) and are in line with those obtained in the studies by (Anggadini 2015;Hla and Teru 2015;Mndzebele 2012;Susanto 2016).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Regarding the first objective, which is aimed to analyze the influence of quality of ICS on quality of AIS, the results show that there is a positive and significant relationship between quality of ICS and quality of AIS, and that the first variable explains 28.4% of the variance of the second variable. The results support the first research hypothesis (H1) and are in line with those obtained in the studies by (Anggadini 2015;Hla and Teru 2015;Mndzebele 2012;Susanto 2016).…”
Section: Discussionsupporting
confidence: 91%
“…This author verifies that the quality of ICS has a positive and significant relationship on quality of AIS, and that the first variable has a 25% influence on the second. However, Anggadini (2015) verifies that top management supports and ICS significantly influence quality of AIS, with a coefficient of determination of 0.72.…”
Section: Discussion Of Resultsmentioning
confidence: 94%
“…Several works have been dedicated to investigating the association between IQ and the use of IT but such research has reported mixed findings without a solid conclusion. In related studies, Anggadini [39] revealed that information quality significantly impacts AIS use in the context of organizations in Indonesia, while Alzoubi [40] examined the use of AIS in the Jordanian context. In the latter study, the author distributed copies of the instrument to financial accountants and managers of the firms focused on and, based on the results, information quality significantly impacted AIS.…”
Section: Information Qualitymentioning
confidence: 99%
“…A controlled study found that companies with internal control deficiencies at the corporate-level exhibited more robust accounting information after the enactment of SOX, but there was no significant difference in the robustness of accounting between companies with internal control deficiencies at the operational level and companies with effective internal controls. For example, [ 10 ] studied 4441 companies' financial data before and after the Act and found that companies were more prudent before the implementation of the Act, as evidenced by later recognition of earnings and earlier recognition of losses.…”
Section: Related Workmentioning
confidence: 99%